Systematic assessment of environmental risk factors for bipolar disorder : an umbrella review of systematic reviews and meta- analyses - Bortolato, Beatrice (2017)
Objectives: The pathophysiology of bipolar disorder is likely to involve both genetic and environmental risk factors. In our study, we aimed to perform a systematic search of environmental risk factors for BD. In addition, we assessed possible hints of bias in this literature, and identified risk factors supported by high epidemiological credibility. Methods: We searched the Pubmed/MEDLINE, EMBASE and PsycInfo databases up to 7 October 2016 to identify systematic reviews and meta-analyses of observational studies that assessed associations between putative environmental risk factors and BD. For each meta-analysis, we estimated its summary effect size by means of both random-and fixed-effects models, 95% confidence intervals (CIs), the 95% prediction interval, and heterogeneity. Evidence of small-study effects and excess of significance bias was also assessed.Results: Sixteen publications met the inclusion criteria (seven meta-analyses and nine qualitative systematic reviews). Fifty-one unique environmental risk factors for BD were evaluated. Six meta-analyses investigated associations with a risk factor for BD. Only irritable bowel syndrome (IBS) emerged as a risk factor for BD supported by convincing evidence (k=6; odds ratio [OR]=2.48; 95% CI=2.35−2.61; P<.001), and childhood adversity was supported by highly suggestive evidence. Asthma and obesity were risk factors for BD supported by suggestive evidence, and seropositivity to Toxoplasma gondii and a history of head injury were supported by weak evidence. Conclusions: Notwithstanding that several environmental risk factors for BD were identified, few meta-analyses of observational studies were available. Therefore, further well-designed and adequately powered studies are necessary to map the environmental risk factors for BD.